Análise de experiência em formação de formadores em organizações da sociedade civil - Lima, Franklin Felix de (2016)
This study investigates the significant elements of an institutional strengthening program, developed by a civil society organization based in São Paulo with national presence, from the look of the participants, ie those who have gone through training, experienced the developed methodology and contributed to the realization of the Motirõ Institutional Strengthening Program. To achieve this purpose, we have deepened the analysis of the strategic role in social change played by organizations participating in the program, and verify the contribution to the culture of lifelong learning in the organization, the contribution to the strengthening of the participants as multipliers within the organization, the effects and impacts in the participating organization of training and of the importance of coordinated actions and networking. The theoretical approach that supports the reflections converges for studies on training of formators and the different elements that sustain it, such as popular education, learning and public policy from the Freirian view corroborated by authors like Dermeval Saviani, Laurence Bardin, Anísio Teixeira among others. Qualitative research was conducted in the city of Recife in Pernambuco, with members and managers of organizations participating in the program, which took place in the Brazilian Northeast from 2012 to 2015 in four editions. Because there are few reports of studies like this in the Northeast and lack of formal evaluation able to translate impressions and learning of the participants, there were significant issues relating to the Motirõ Program operation that need addressing. Among the findings, there were positive results in the development of networking job directly related to the strength of the articulation of interpersonal relationships, demonstrating the care of the affective bonds and mutual support